2020
DOI: 10.1128/jcm.01886-19
|View full text |Cite
|
Sign up to set email alerts
|

Single-Locus-Sequence-Based Typing of the mgpB Gene Reveals Transmission Dynamics in Mycoplasma genitalium

Abstract: Sexually transmitted infections (STIs) by Mycoplasma genitalium are a major problem worldwide, especially given their marked and rapid propensity for developing antimicrobial resistance. Since very few treatment options exist, clinicians face an important challenge in the management of the infection. In this scenario, little is known regarding the transmission dynamics of M. genitalium and the epidemiology of antimicrobial resistance. This mgpB-based molecular typing study, conducted among 54 asymptomatically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…Despite the low rate of non-MSM with a confirmed mgpB type among the patients ( n = 8, 13.8%), one of two women who have sex with men (WSM) and the men who have sex with women (MSW) belonged to cluster 2 (exception: woman #35), supporting the hypothesis of a largely independent circulation of genotypes in both groups. This was also shown in a recent study [ 27 ]. After the investigation of strains sampled between the years 2014 and 2016 in Dresden (31.6%) and between 2017 and 2018 in Berlin (38.6%), type 4 was also the most common mgpB type [ 21 , 28 ].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Despite the low rate of non-MSM with a confirmed mgpB type among the patients ( n = 8, 13.8%), one of two women who have sex with men (WSM) and the men who have sex with women (MSW) belonged to cluster 2 (exception: woman #35), supporting the hypothesis of a largely independent circulation of genotypes in both groups. This was also shown in a recent study [ 27 ]. After the investigation of strains sampled between the years 2014 and 2016 in Dresden (31.6%) and between 2017 and 2018 in Berlin (38.6%), type 4 was also the most common mgpB type [ 21 , 28 ].…”
Section: Resultssupporting
confidence: 89%
“…After the investigation of strains sampled between the years 2014 and 2016 in Dresden (31.6%) and between 2017 and 2018 in Berlin (38.6%), type 4 was also the most common mgpB type [ 21 , 28 ]. Furthermore, the results of reports from France and Spain demonstrated rates of type 4 strains of 23.8% and 27.8%, respectively [ 20 , 27 ]. All these studies included a high percentage of MSM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that transmission is not the sole cause of antibiotic-resistance spread in this study group; rather, parC SNPs have likely arisen independently during fluoroquinolone treatment. Similar findings were reported in studies by Fernandez-Huerta et al (2020) andSweeney et al (2020) where they both observed de novo acquisition of parC mutations[47,48]. Insufficient information was available to analyse the distribution of gyrA SNPs.The most common STs observed in this study were ST-A/105 and ST-C/4.…”
supporting
confidence: 86%
“…In several studies, a large distribution of M. genitalium genotypes was found among macrolide-and fluoroquinolone-resistant isolates, supporting the hypothesis of a multiclonal spread of resistance in this species, rather than the spread of a single or of a few resistant clones. This multiclonal spread is likely associated with the consequences of antibiotic selection pressure on diverse independent M. genitalium strains [161][162][163].…”
Section: Critical Cases Of Multiple Drugmentioning
confidence: 99%